2020
DOI: 10.1186/s13071-020-04119-w
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation networks in spargana of Spirometra erinaceieuropaei revealed by phosphoproteomic analysis

Abstract: Background Sparganosis caused by Spirometra erinaceieuropaei spargana is a zoonotic parasitic infection that has been reported in many countries, including China, Japan, Thailand and Korea, as well as European countries and the USA. The biological and clinical significance of the parasite have previously been reported. Although the genomic and transcriptomic analysis of S. erinaceieuropaei provided insightful views about the development and pathogenesis of this species, little knowledge has been acquired in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In that case, future developmental phosphoproteomics analyses supplementing with knockdown experiments are needed to confirm whether the hyper-phosphorylated glycogen synthase correlates with the development and survival of F. gigantica or not in a certain stage. On the other hand, previous studies had found that the mutations in important phosphosites might result in the termination of the phosphorylation, leading to disorders of biological processes (Liu et al 2020b ). So an additional point mutation in glycogen synthase will be used to test the essentiality of the serine or threonine phosphorylation and further explore its functional domains.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In that case, future developmental phosphoproteomics analyses supplementing with knockdown experiments are needed to confirm whether the hyper-phosphorylated glycogen synthase correlates with the development and survival of F. gigantica or not in a certain stage. On the other hand, previous studies had found that the mutations in important phosphosites might result in the termination of the phosphorylation, leading to disorders of biological processes (Liu et al 2020b ). So an additional point mutation in glycogen synthase will be used to test the essentiality of the serine or threonine phosphorylation and further explore its functional domains.…”
Section: Discussionmentioning
confidence: 98%
“…The lysate debris were eliminated by centrifugation at 12,000 g for 30 min at 4 ℃, and individual supernatants were collected and conducted to determine the protein concentration by a bicinchoninic acid (BCA) protein assay kit (Thermo Fisher Scientific, USA). Protein digestion was carried out as previously described (Liu et al 2020b ; Ren et al 2018 ), with some modifications. Briefly, 300 μg protein sample was reduced with 20 mM dithiothreitol at 56 ℃ for 30 min, followed by alkylation with 100 mM iodoacetamide at room temperature for 30 min, then dissolved into urea solution with the addition of 25 mM NH 4 HCO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein spots which showed immune response were characterized by MALDI-TOF/TOF-MS. The recent study on S. erinaceieuropaei sparanga described site-specific phosphoproteome, with the purpose of describing the global phosphorylation status of spargana [ 82 ]. A total of 1758 spargana proteins were identified, where 3228 phosphopeptides and 3461 phosphorylation sites were described among.…”
Section: Discovery Approach—description Of the Selected Fbps And Tmentioning
confidence: 99%
“…Another reason is the high infection rate of frogs and snakes in China. A survey showed that 14.3% (31/217) and 91.7% (344/375) of frogs and snakes, respectively, were infected in Hunan Province [11,12].…”
Section: Introductionmentioning
confidence: 99%